Inferior natal teeth detected within the first hours of life: report case (Research, Society and Development, 2020)
The objective of this article is to report a clinical case of a patient with a natal tooth presenting the clinical characteristics, causes and treatment. The case report shows a female patient, new born with 30 hours of life, presenting respiratory distress and severe hypothermia (31.3ºC) after delivery, soon resolved by the responsible medical team. In the first hours of life, the presence of two lower teeth in the dental arch was detected and pointed out for making breast feeding difficult, been referred to the Dentistry service of the University Hospital Lauro Wanderley. Intraoral physical examination showed no lesions or trauma to the mucosa, and the presence of two teeth in the region of the lower central incisors that showed accentuated mobility was verified. Due to the difficulty in breastfeeding, tooth mobility and concern about teeth being aspirated, it became necessary to remove the elements. The procedure was performed under topical local anesthesia with 5% Lidocaine spray, applied on a cotton swab. Then, a Molt detacher was used, removing part of the mucosa that covered the teeth and the excision of the two dental elements was performed. Suture was not necessary and there were no complications during the surgical procedure. It is concluded that this rare condition requires multidisciplinary work between the team responsible for the pregnant woman and the new born, who must recognize this anomaly as soon as possible in order to be able to refer to a dentist to define together what is the best conduct.